Aluminum electrolytic capacitor and method for manufacturing the same

By using six-stage-degraded anode foil and specific electrolyte, combined with an improved packaging process, the problem of reduced capacity and possible explosion of aluminum electrolytic capacitors in high temperature environments is solved, achieving higher high temperature resistance and longer service life.

CN115938805BActive Publication Date: 2025-03-07ZHAOQING BERYL ELECTRONICS TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211363076.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-02
Publication Date
2025-03-07
Estimated Expiration
2042-11-02

AI Technical Summary

Technical Problem

Existing aluminum electrolytic capacitors tend to increase the viscosity of the electrolyte in high temperature and harsh environments, increase the equivalent series resistance, resulting in a decrease in capacity and possible explosion.

Method used

The six-stage-degraded anode foil and specific components are used to ensure the stability of the electrolyte and the sealing of the packaging.

Benefits of technology

It improves the high temperature resistance of the capacitor, reduces leakage current and product losses, prevents high-pressure explosions caused by electrolyte boiling or electrochemical processes, and extends the service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0004042591990000051
    Figure GDA0004042591990000051
  • Figure GDA0004042591990000071
    Figure GDA0004042591990000071
  • Figure GDA0004042591990000081
    Figure GDA0004042591990000081
Patent Text Reader

Abstract

The invention discloses an aluminum electrolytic capacitor and a manufacturing method thereof. The manufacturing method comprises the following steps: Step S1, making a core package, the specific capacitance of the anode foil is 0.67-0.70 μF / cm 2 , thickness 110-125 μm, specific volume discrete rate ≤10%, tensile strength ≥16.7 N / cm; step S2, drying treatment; step S3, electrolyte impregnation: immerse the core package dried in step S2 into the electrolyte for impregnation treatment, the electrolyte is composed of the following components by mass percentage: main solvent 45%-68%, auxiliary solvent 15%-25%, solute 8%-15%, additive 5%-12%, getter 0.8%-2%, repair agent 0.3%-1%; step S4, heating polymerization; step S5, packaging step: put the core package polymerized in step S4 into the shell and seal it with a rubber plug; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 4.0±0.3 mm, and the glue insertion depth of the curling edge is 40%-60% of the thickness of the rubber plug; step S6, aging step. The aluminum electrolytic capacitor of the present invention not only reduces leakage current and product loss, but also improves the product's ability to withstand large ripple currents.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of capacitors, and in particular to an aluminum electrolytic capacitor and a manufacturing method thereof. Background Art

[0002] In Japan, frequency conversion control is the standard technology for air conditioners and refrigerators, and frequency conversion air conditioners account for 80% of the entire air conditioner market. At present, the global market size is relatively stable, with consumer electronics applications accounting for as high as 35%, and domestic consumption accounting for a larger proportion than other regions. Computer and peripheral applications account for 22%, and industrial, power and lighting applications account for 18%. Japanese companies still dominate the supplier market, with Nichicon, Rubycon, and Panasonic accounting for more than 50% of the global share. Domestic companies Aihua Group and Jianghai Co., Ltd. have a relatively small share, but are expanding year by year. According to the current requirements of domestic frequency conversion air conditioner manufacturers and the situation of similar products abroad, the technical characteristics of large aluminum electrolytic capacitors for frequency conversion air conditioners are: high reliability and safety, explosion-proof bottom of aluminum shell, and zero-defect products from the perspective of the whole machine; the use conditions of capacitors are harsh, because they are generally installed in dry outdoor hanging units, the ambient temperature varies greatly, and most of the whole machines are in intermittent operation, so the electrical performance of capacitors is required to be very stable.

[0003] In the past, there was a misunderstanding about the application of variable frequency air conditioner products. It was always believed that air conditioners were used seasonally and for a short time, and the cost pressure was high. Therefore, in the past, when selecting models, people generally chose 85℃ ordinary products, 400V ordinary products, 450V ordinary products, etc. In fact, for air conditioner applications, we must first fully consider the worst conditions of the use environment, such as: (1) Installed on the south balcony, exposed to the sun for a long time in summer, resulting in a relatively high ambient temperature of the product; (2) For some remote areas, due to the large fluctuation of the grid voltage, overvoltage or overcurrent will occur, which will cause serious heating inside the product, and eventually lead to failure of large capacitors; (3) If the surrounding air pollution is relatively severe, such as the long-term presence of some halogen-containing gases, it will also seriously affect the service life of the capacitor; (4) Now many families have good conditions, and the air conditioner is turned on for a long time in winter and summer, which has exceeded the previous design assumptions. With the development of power electronic devices, variable frequency technology is also developing continuously; therefore, it is necessary to develop an aluminum electrolytic capacitor that can meet the new needs of air conditioner use.

[0004] In the prior art, when the electrolyte of an aluminum electrolytic capacitor evaporates more and the solution becomes thicker, the resistivity increases due to the increased viscosity, which increases the equivalent series resistance of the working electrolyte, resulting in a significant increase in capacitor loss and an increase in the loss angle. For example, for an electrolytic capacitor with an operating temperature of 105°C, when its maximum core package temperature is higher than 125°C, the viscosity of the electrolyte increases sharply, and the ESR of the electrolyte increases nearly tenfold; the increased equivalent series resistance generates greater heat, causing greater volatilization of the electrolyte. This cycle repeats itself, causing the capacity of the aluminum electrolytic capacitor to drop sharply, and may even cause an explosion. Summary of the invention

[0005] In order to make up for the defects of the prior art, the present invention provides an aluminum electrolytic capacitor and a manufacturing method thereof.

[0006] The technical problem to be solved by the present invention is achieved through the following technical solutions:

[0007] A method for manufacturing an aluminum electrolytic capacitor comprises the following steps:

[0008] Step S1, making a core package: inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; wherein the specific capacitance of the anode foil is 0.67-0.70 μF / cm 2 , thickness 110~125μm, specific volume discreteness ≤10%, tensile strength ≥16.7N / cm;

[0009] Step S2, drying treatment: baking and drying the wound core package;

[0010] Step S3, electrolyte impregnation: immerse the core package dried in step S2 into an electrolyte for impregnation treatment, wherein the electrolyte is composed of the following components by mass percentage: 45% to 68% of a main solvent, 15% to 25% of an auxiliary solvent, 8% to 15% of a solute, 5% to 12% of an additive, 0.8% to 2% of a getter, and 0.3% to 1% of a repair agent;

[0011] Step S4, heating and polymerization: heating and polymerization of the core package impregnated in step S3;

[0012] Step S5, packaging step: wrapping the core polymerized in step S4 into a shell and sealing with a rubber plug; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled to be 4.0±0.3mm, and the glue insertion depth of the curling edge is 40% to 60% of the thickness of the rubber plug;

[0013] Step S6, aging step;

[0014] The aluminum electrolytic capacitor obtained by the manufacturing method is applied to a central air-conditioning control panel.

[0015] As a preferred embodiment of the method for manufacturing an aluminum electrolytic capacitor provided by the present invention, the main solvent is composed of the following components by mass percentage: 45-67% ethylene glycol, 22-35% glycerol, and 5-20% diethylene glycol.

[0016] As a preferred embodiment of the method for manufacturing an aluminum electrolytic capacitor provided by the present invention, the auxiliary solvent is composed of the following components by mass percentage: 50-62% of ammonium dicarboxylate, 18-30% of phosphotungstic acid, and 10-25% of polyethylene glycol.

[0017] As a preferred implementation of the method for manufacturing an aluminum electrolytic capacitor provided by the present invention, the solute is composed of the following components by mass percentage: 35-55% of ammonium adipate, 15-25% of ammonium acetate, 10-22% of citric acid, 5-14% of 1.10-ammonium sebacate, and 3-10% of 1.6-dodecanedioic acid.

[0018] As a preferred embodiment of the method for manufacturing an aluminum electrolytic capacitor provided by the present invention, the additive is composed of the following components by mass percentage: 30-45% nitrotrinitroborane, 18-32% 8-hydroxyquinoline, 12-25% nitrilotriacetic acid, and 5-15% tributyl phosphate.

[0019] As a preferred embodiment of the method for manufacturing an aluminum electrolytic capacitor provided by the present invention, the repair agent is composed of the following components by mass percentage: 42-70% polyvinyl alcohol, 18-30% ammonium sebacate, 3-18% sodium hydroxide, and 1-8% sodium hypophosphite.

[0020] As a preferred embodiment of the method for manufacturing an aluminum electrolytic capacitor provided by the present invention, the anode foil is an anode foil that has undergone six-stage chemical formation treatment.

[0021] As a preferred implementation of the method for manufacturing an aluminum electrolytic capacitor provided by the present invention, the rubber plug is prepared by mixing Teflon-coated bakelite with EPDM rubber.

[0022] As a preferred embodiment of the method for manufacturing an aluminum electrolytic capacitor provided by the present invention, the electrolytic paper is wood pulp fiber.

[0023] An aluminum electrolytic capacitor is manufactured by any of the above manufacturing methods.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] The aluminum electrolytic capacitor prepared by the manufacturing method provided by the present invention not only reduces leakage current and product loss, but also improves the product's ability to withstand large ripple currents. In a high-temperature environment, as the use time increases, the electrolyte is gradually consumed and volatilized. For this reason, the present invention develops a new working electrolyte with high conductivity, high flash voltage, strong repair ability, and stable high-temperature performance, which reduces product loss and prevents the aluminum electrolytic capacitor from exploding due to internal high-temperature boiling gas or gas generated by electrochemical processes, thereby stabilizing the product's electrical properties and improving the product's ability to withstand large ripple currents. The inventors also found that the above-mentioned electrolyte needs to be matched with a specific anode foil to be fully displayed. The specific anode foil is an anode foil that has been subjected to six-stage chemical formation treatment and has a specific capacitance of 0.67-0.70 μF / cm 2 , thickness 110~125μm, specific volume discrete rate ≤10%, tensile strength ≥16.7N / cm, improve the effect of high temperature to deteriorate the oxide film medium, resulting in increased leakage current and accelerated destruction of dielectric insulation performance, stabilizing the electrical performance of the product. The inventor further improved the packaging process: the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 4.0±0.3mm, and the glue insertion depth of the curling edge is 40%~60% of the thickness of the rubber plug, so that the curling edge is tightly attached to the rubber surface of the rubber plug, which can better lock the electrolyte, ensure that the electrolyte will not be gradually consumed and volatilized at high temperature and with the increase of use time, so that the life of the product is improved. DETAILED DESCRIPTION

[0026] The present invention is described in detail below with reference to the examples. The examples are only preferred embodiments of the present invention and are not intended to limit the present invention.

[0027] Example 1

[0028] A method for manufacturing an aluminum electrolytic capacitor used in a central air conditioning control panel comprises the following steps:

[0029] Step S1, making a core package: inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; wherein the anode foil is a positive foil that has undergone six-stage chemical treatment, has a withstand voltage of 590VF, and has a specific capacitance of 0.67μF / cm 2 , thickness 110μm, specific volume discreteness rate: 8%, tensile strength: 18N / cm;

[0030] The electrolytic paper is wood pulp fiber;

[0031] Step S2, drying treatment: baking and drying the wound core package;

[0032] Step S3, electrolyte impregnation: immerse the core package dried in step S2 into the electrolyte for impregnation treatment, wherein the electrolyte is composed of the following components by mass percentage: 45% main solvent, 25% auxiliary solvent, 15% solute, 12% additive, 2% getter, and 1% repair agent; wherein,

[0033] The main solvent is composed of the following components by mass percentage: 45% ethylene glycol, 35% propylene glycol, and 20% diethylene glycol;

[0034] The auxiliary solvent is composed of the following components by mass percentage: 50% ammonium dicarboxylate, 25% phosphotungstic acid, and 25% polyethylene glycol;

[0035] The solute is composed of the following components by mass percentage: 35% ammonium adipate, 25% ammonium acetate, 22% citric acid, 14% 1.10-ammonium sebacate, and 4% 1.6-dodecanedioic acid;

[0036] The additive is composed of the following ingredients by mass percentage: 30% nitrotrinitroborane, 32% 8-hydroxyquinoline, 23% nitrilotriacetic acid, and 15% tributyl phosphate;

[0037] The repair agent is composed of the following ingredients by mass percentage: 45% polyvinyl alcohol, 30% ammonium sebacate, 18% sodium hydroxide, and 7% sodium hypophosphite;

[0038] Step S4, heating and polymerization: heating and polymerization of the core package impregnated in step S3;

[0039] Step S5, packaging step: wrapping the core polymerized in step S4 into a shell and sealing with a rubber plug, wherein the rubber plug is prepared by mixing Teflon-coated bakelite with EPDM rubber; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 4.0 mm, and the glue insertion depth of the curling edge is 40% of the thickness of the rubber plug;

[0040] Step S6: Aging step.

[0041] The aluminum electrolytic capacitor prepared in Example 1 was subjected to a ripple life test of 2000 hours and a 105° C. high-temperature storage test of 1000 hours. The performance test after the test is shown in Table 1 below.

[0042]

[0043] Example 2

[0044] A method for manufacturing an aluminum electrolytic capacitor used in a central air conditioning control panel comprises the following steps:

[0045] Step S1, making a core package: inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; wherein the anode foil is a positive foil that has undergone six-stage chemical treatment, has a withstand voltage of 590VF, and has a specific capacitance of 0.67μF / cm 2 , thickness 110μm, specific volume discreteness: 7%, tensile strength: 20N / cm.

[0046] The electrolytic paper is wood pulp fiber;

[0047] Step S2, drying treatment: baking and drying the wound core package;

[0048] Step S3, electrolyte impregnation: immerse the core package dried in step S2 into the electrolyte for impregnation treatment, wherein the electrolyte is composed of the following components by mass percentage: 55% main solvent, 22% auxiliary solvent, 12% solute, 9% additive, 1.7% getter, and 0.3% repair agent; wherein,

[0049] The main solvent is composed of the following components by mass percentage: 50% ethylene glycol, 32% propylene glycol, and 18% diethylene glycol;

[0050] The auxiliary solvent is composed of the following components by mass percentage: 52% ammonium dicarboxylate, 28% phosphotungstic acid, and 20% polyethylene glycol;

[0051] The solute is composed of the following components by mass percentage: 38% ammonium adipate, 22% ammonium acetate, 20% citric acid, 10% 1.10-ammonium sebacate, and 10% 1.6-dodecanedioic acid;

[0052] The additive is composed of the following ingredients by mass percentage: 32% nitrotrinitroborane, 30% 8-hydroxyquinoline, 25% nitrilotriacetic acid, and 13% tributyl phosphate;

[0053] The repair agent is composed of the following ingredients by mass percentage: 48% polyvinyl alcohol, 28% ammonium sebacate, 20% sodium hydroxide, and 4% sodium hypophosphite;

[0054] Step S4, heating and polymerization: heating and polymerization of the core package impregnated in step S3;

[0055] Step S5, packaging step: wrapping the core polymerized in step S4 into a shell and sealing with a rubber plug, wherein the rubber plug is prepared by mixing Teflon-coated bakelite with EPDM rubber; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 4.1 mm, and the glue insertion depth of the curling edge is 45% of the thickness of the rubber plug;

[0056] Step S6: Aging step.

[0057] The aluminum electrolytic capacitor prepared in Example 2 was subjected to a ripple life test of 2000 hours and a 105° C. high temperature storage test of 1000 hours. The performance test after the test is shown in Table 2 below.

[0058]

[0059] Example 3

[0060] A method for manufacturing an aluminum electrolytic capacitor used in a central air conditioning control panel comprises the following steps:

[0061] Step S1, making a core package: inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; wherein the anode foil is a positive foil that has undergone six-stage chemical treatment, and its withstand voltage is 590VF, and the specific capacitance of the anode foil is 0.68μF / cm 2 , thickness 115μm, specific volume discreteness: 9%, tensile strength: 18N / cm;

[0062] The electrolytic paper is wood pulp fiber;

[0063] Step S2, drying treatment: baking and drying the wound core package;

[0064] Step S3, electrolyte impregnation: immerse the core package dried in step S2 into the electrolyte for impregnation treatment, wherein the electrolyte is composed of the following components by mass percentage: 56% main solvent, 20% auxiliary solvent, 14% solute, 8% additive, 1.5% getter, and 0.5% repair agent; wherein,

[0065] The main solvent is composed of the following components by mass percentage: 55% ethylene glycol, 30% propylene glycol, and 15% diethylene glycol;

[0066] The auxiliary solvent is composed of the following components by mass percentage: 55% ammonium dicarboxylate, 25% phosphotungstic acid, and 20% polyethylene glycol;

[0067] The solute is composed of the following components by mass percentage: 40% ammonium adipate, 20% ammonium acetate, 20% citric acid, 12% 1.10-ammonium sebacate, and 8% 1.6-dodecanedioic acid;

[0068] The additive is composed of the following ingredients by mass percentage: 38% nitrotrinitroborane, 28% 8-hydroxyquinoline, 24% nitrilotriacetic acid, and 10% tributyl phosphate;

[0069] The repair agent is composed of the following ingredients by mass percentage: 52% polyvinyl alcohol, 25% ammonium sebacate, 17% sodium hydroxide, and 6% sodium hypophosphite;

[0070] Step S4, heating and polymerization: heating and polymerization of the core package impregnated in step S3;

[0071] Step S5, packaging step: wrapping the core polymerized in step S4 into a shell and sealing with a rubber plug, wherein the rubber plug is prepared by mixing Teflon-coated bakelite with EPDM rubber; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 3.8 mm, and the glue insertion depth of the curling edge is 60% of the thickness of the rubber plug;

[0072] Step S6: Aging step.

[0073] The aluminum electrolytic capacitor prepared in Example 3 was subjected to a ripple life test of 2000 hours and a 105° C. high-temperature storage test of 1000 hours. The performance test after the test is shown in Table 3 below.

[0074]

[0075] Example 4

[0076] A method for manufacturing an aluminum electrolytic capacitor used in a central air conditioning control panel comprises the following steps:

[0077] Step S1, making a core package: inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; wherein the anode foil is a positive foil that has undergone six-stage chemical treatment, has a withstand voltage of 590VF, and has a specific capacitance of 0.69μF / cm 2 , thickness 120μm, specific volume discreteness: 9%, tensile strength: 17.6N / cm;

[0078] The electrolytic paper is wood pulp fiber;

[0079] Step S2, drying treatment: baking and drying the wound core package;

[0080] Step S3, electrolyte impregnation: immerse the core package dried in step S2 into the electrolyte for impregnation treatment, wherein the electrolyte is composed of the following components by mass percentage: 60% main solvent, 21% auxiliary solvent, 12% solute, 5% additive, 1% getter, and 1% repair agent; wherein,

[0081] The main solvent is composed of the following components by mass percentage: 60% ethylene glycol, 28% propylene glycol, and 12% diethylene glycol;

[0082] The auxiliary solvent is composed of the following components by mass percentage: 60% ammonium dicarboxylate, 30% phosphotungstic acid, and 10% polyethylene glycol;

[0083] The solute is composed of the following components by mass percentage: 45% ammonium adipate, 18% ammonium acetate, 18% citric acid, 12% 1.10-ammonium sebacate, and 7% 1.6-dodecanedioic acid;

[0084] The additive is composed of the following ingredients by mass percentage: 42% nitrotrinitroborane, 18% 8-hydroxyquinoline, 25% nitrilotriacetic acid, and 15% tributyl phosphate;

[0085] The repair agent is composed of the following components by mass percentage: 58% polyvinyl alcohol, 22% ammonium sebacate, 12% sodium hydroxide, and 8% sodium hypophosphite;

[0086] Step S4, heating and polymerization: heating and polymerization of the core package impregnated in step S3;

[0087] Step S5, packaging step: wrapping the core polymerized in step S4 into a shell and sealing with a rubber plug, wherein the rubber plug is prepared by mixing Teflon-coated bakelite with EPDM rubber; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 4.2 mm, and the glue insertion depth of the curling edge is 50% of the thickness of the rubber plug;

[0088] Step S6: Aging step.

[0089] The aluminum electrolytic capacitor prepared in Example 4 was subjected to a ripple life test of 2000 hours and a 105° C. high-temperature storage test of 1000 hours. The performance test after the test is shown in Table 4 below.

[0090]

[0091] Example 5

[0092] A method for manufacturing an aluminum electrolytic capacitor used in a central air conditioning control panel comprises the following steps:

[0093] Step S1, making a core package: inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; wherein the anode foil is a positive foil that has undergone six-stage chemical treatment, has a withstand voltage of 590VF, and has a specific capacitance of 0.70μF / cm 2 , thickness 125μm, specific volume discreteness: 6%, tensile strength: 19.6N / cm;

[0094] The electrolytic paper is wood pulp fiber;

[0095] Step S2, drying treatment: baking and drying the wound core package;

[0096] Step S3, electrolyte impregnation: immerse the core package dried in step S2 into the electrolyte for impregnation treatment, wherein the electrolyte is composed of the following components by mass percentage: 68% main solvent, 15% auxiliary solvent, 8% solute, 7.2% additive, 0.8% getter, and 1% repair agent; wherein,

[0097] The main solvent is composed of the following components by mass percentage: 65% ethylene glycol, 22% propylene glycol, and 13% diethylene glycol;

[0098] The auxiliary solvent is composed of the following components by mass percentage: 58% ammonium dicarboxylate, 20% phosphotungstic acid, and 22% polyethylene glycol;

[0099] The solute is composed of the following components by mass percentage: 50% ammonium adipate, 16% ammonium acetate, 20% citric acid, 9% 1.10-ammonium sebacate, and 5% 1.6-dodecanedioic acid;

[0100] The additive is composed of the following ingredients by mass percentage: 45% nitrotrinitroborane, 32% 8-hydroxyquinoline, 12% nitrilotriacetic acid, and 11% tributyl phosphate;

[0101] The repair agent is composed of the following ingredients by mass percentage: 65% polyvinyl alcohol, 27% ammonium sebacate, 3% sodium hydroxide, and 5% sodium hypophosphite;

[0102] Step S4, heating and polymerization: heating and polymerization of the core package impregnated in step S3;

[0103] Step S5, packaging step: wrapping the core polymerized in step S4 into a shell and sealing with a rubber plug, wherein the rubber plug is prepared by mixing Teflon-coated bakelite with EPDM rubber; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 4.3 mm, and the glue insertion depth of the curling edge is 55% of the thickness of the rubber plug;

[0104] Step S6: Aging step.

[0105] The aluminum electrolytic capacitor prepared in Example 5 was subjected to a ripple life test of 2000 hours and a 105° C. high temperature storage test of 1000 hours. The performance test after the test is shown in Table 5 below.

[0106]

[0107] Example 6

[0108] A method for manufacturing an aluminum electrolytic capacitor used in a central air conditioning control panel comprises the following steps:

[0109] Step S1, making a core package: inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; wherein the anode foil is a positive foil that has undergone six-stage chemical treatment, has a withstand voltage of 590VF, and has a specific capacitance of 0.70μF / cm 2 , thickness 122μm, specific volume discreteness: 10%, tensile strength: 17N / cm;

[0110] The electrolytic paper is wood pulp fiber;

[0111] Step S2, drying treatment: baking and drying the wound core package;

[0112] Step S3, electrolyte impregnation: immerse the core package dried in step S2 into an electrolyte for impregnation treatment, wherein the electrolyte is composed of the following components by mass percentage:

[0113] Main solvent 65%, auxiliary solvent 15%, solute 10%, additive 8.5%, getter 0.8%, repair agent 0.7%; among which,

[0114] The main solvent is composed of the following components by mass percentage: 67% ethylene glycol, 28% propylene glycol, and 5% diethylene glycol;

[0115] The auxiliary solvent is composed of the following components by mass percentage: 62% ammonium dicarboxylate, 18% phosphotungstic acid, and 20% polyethylene glycol;

[0116] The solute is composed of the following components by mass percentage: 55% ammonium adipate, 15% ammonium acetate, 22% citric acid, 5% 1.10-ammonium sebacate, and 3% 1.6-dodecanedioic acid;

[0117] The additive is composed of the following ingredients by mass percentage: 45% nitrotrinitroborane, 22% 8-hydroxyquinoline, 25% nitrilotriacetic acid, and 8% tributyl phosphate;

[0118] The repair agent is composed of the following ingredients by mass percentage: 70% polyvinyl alcohol, 18% ammonium sebacate, 11% sodium hydroxide, and 1% sodium hypophosphite;

[0119] Step S4, heating and polymerization: heating and polymerization of the core package impregnated in step S3;

[0120] Step S5, packaging step: wrapping the core polymerized in step S4 into a shell and sealing with a rubber plug, wherein the rubber plug is prepared by mixing Teflon-coated bakelite with EPDM rubber; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 3.7 mm, and the glue insertion depth of the curling edge is 58% of the thickness of the rubber plug;

[0121] Step S6: Aging step.

[0122] The aluminum electrolytic capacitor prepared in Example 6 was subjected to a ripple life test of 2000 hours and a 105° C. high-temperature storage test of 1000 hours. The performance test after the test is shown in Table 6 below.

[0123]

[0124] Comparative Example 1

[0125] The manufacturing method of comparative example 1 is basically the same as that of embodiment 1, except that the anode foil is a six-stage chemically treated anode foil with a withstand voltage of 590 VF and a specific capacitance of 0.72 μF / cm2 , thickness 130μm, specific volume discreteness 14%, tensile strength 15N / cm.

[0126] The aluminum electrolytic capacitor prepared in Comparative Example 1 was subjected to a ripple life test of 2000 hours and a 105° C. high-temperature storage test of 1000 hours. The performance test after the test is shown in Table 7 below.

[0127]

[0128] As shown in Table 7, the anode foil is a six-stage chemically treated anode foil with a withstand voltage of 590 VF and a specific capacitance of 0.72 μF / cm 2 , thickness 130μm, specific capacitance dispersion rate 14%, tensile strength 15N / cm. This results in large loss value and leakage current of the capacitor, poor stability, and not only obvious increase in DF and ESR after ripple life test, but also slight bulging of the aluminum shell; high temperature deteriorates the oxide film dielectric, causing leakage current to increase and accelerate the destruction of dielectric insulation performance. After high temperature storage test, leakage current increases significantly.

[0129] Comparative Example 2

[0130] The manufacturing method of comparative example 2 is basically the same as that of example 1, except that the anode foil is a five-stage chemically treated anode foil with a withstand voltage of 590 VF and a specific capacitance of 0.6 μF / cm 2 , thickness 100μm.

[0131] The aluminum electrolytic capacitor prepared in Comparative Example 2 was subjected to a ripple life test of 2000 hours and a 105° C. high-temperature storage test of 1000 hours. The performance test after the test is shown in Table 8 below.

[0132]

[0133] As shown in Table 8, the anode foil is a six-stage chemically treated anode foil with a withstand voltage of 590 VF and a specific capacitance of 0.6 μF / cm 2 , thickness 100μm. Although the ESR will be low, it will cause the leakage current of the capacitor to be too large. After the ripple life test, not only the capacity decreases, the DF increase is obvious, but also the aluminum shell bulges; after the high temperature storage test, the leakage current increases significantly.

[0134] Comparative Example 3

[0135] The manufacturing method of comparative example 3 is basically the same as that of embodiment 1, except that after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 3.4 mm, and the glue penetration depth of the curling edge is 70% of the thickness of the rubber plug.

[0136] The aluminum electrolytic capacitor prepared in Comparative Example 3 was subjected to a ripple life test of 2000 hours and a 105° C. high-temperature storage test of 1000 hours. The performance test after the test is shown in Table 9 below.

[0137]

[0138] It can be seen from Table 9 that after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 3.4mm, and the glue depth of the curling edge is 70% of the thickness of the rubber plug. After the ripple life test, the △C capacity dropped seriously, DF and LC increased greatly, and the aluminum shell bulged; dissection: the element was deformed under pressure, and the foil guide strip contacted with the aluminum foil and sparked.

[0139] Comparative Example 4

[0140] The manufacturing method of comparative example 4 is basically the same as that of embodiment 1, except that after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 5 mm, and the glue penetration depth of the curling edge is 30% of the thickness of the rubber plug.

[0141] The aluminum electrolytic capacitor prepared in Comparative Example 4 was subjected to a ripple life test of 2000 hours and a 105° C. high-temperature storage test of 1000 hours. The performance test after the test is shown in Table 10 below.

[0142]

[0143] As shown in Table 10, after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled at 5mm, and the glue depth of the curling edge is 30% of the thickness of the rubber plug. The curling edge of the aluminum shell is not tightly attached to the rubber surface, which cannot better lock the electrolyte. Under high temperature and with the increase of use time, the electrolyte will gradually consume and volatilize. After the ripple life test, not only the capacity decreases significantly, but also the DF increases significantly; after the high temperature storage test, the leakage current increases significantly.

[0144] Comparative Example 5

[0145] The manufacturing method of comparative example 5 is substantially the same as that of embodiment 1, except that: polyethylene glycol is not added to the auxiliary solvent and 1,6-dodecanedioic acid is not added to the solute. Specifically, the auxiliary solvent is composed of the following components by mass percentage: 50% ammonium dicarboxylate and 50% phosphotungstic acid; the solute is composed of the following components by mass percentage: 35% ammonium adipate, 25% ammonium acetate, 24% citric acid, and 16% 1,10-ammonium sebacate.

[0146] The aluminum electrolytic capacitor prepared in Comparative Example 5 was subjected to a ripple life test of 2000 hours and a 105°C high temperature storage test of 1000 hours. The performance test after the test is shown in Table 11 below.

[0147]

[0148] It can be seen from Table 11 that the auxiliary solvent does not contain polyethylene glycol and the solute does not contain 1,6-dodecanedioic acid; it cannot increase its solubility in ethylene glycol, cannot improve its conductivity, cannot improve its flash voltage, and its conductivity and high temperature resistance are not strong; it cannot work synergistically with polyethylene glycol, resulting in poor high temperature stability, and cannot prevent the gradual consumption and volatilization of the solvent when the internal temperature of the product increases; it cannot repair the damaged oxide film in time, and cannot reduce the leakage current. After the ripple life test, not only the capacity decreases significantly, the DF increase is relatively obvious, and the aluminum shell bulges; after the high temperature storage test, the leakage current increases significantly.

[0149] Comparative Example 6

[0150] The manufacturing method of comparative example 6 is basically the same as that of example 1, except that: the additive does not contain nitrilotriacetic acid and the repair agent does not contain sodium hydroxide or sodium hypophosphite. Specifically, the additive is composed of the following components by mass percentage: 35% nitrotrinitroborane, 40% 8-hydroxyquinoline, and 25% tributyl phosphate; the repair agent is composed of the following components by mass percentage: 45% polyvinyl alcohol and 55% ammonium sebacate.

[0151] The aluminum electrolytic capacitor prepared in Comparative Example 6 was subjected to a ripple life test of 2000 hours and a 105°C high temperature storage test of 1000 hours. The performance test after the test is shown in Table 12 below.

[0152]

[0153] As can be seen from Table 12, the additive does not contain nitrilotriacetic acid and the repair agent does not contain sodium hydroxide or sodium hypophosphite; its formation ability is not strong, and it cannot be complexed with the aluminum ions dissolved in the electrolyte, and cannot effectively prevent the capacitor from prematurely bulging when working under large ripple conditions, causing product failure. It also cannot enhance the strength of the oxide film, and cannot achieve the role of oxide film repair and self-healing, and cannot improve the wettability of the electrolyte to the electrolytic paper, and cannot enhance the penetration of the electrolyte in the holes of the anode foil and the electrolytic paper, so that the product loss cannot be reduced and the product's ability to withstand large ripple current cannot be improved. After the ripple life test, not only the capacity decreased significantly, but also the DF and ESR increased significantly, and the aluminum shell bulged; after the high-temperature storage test, the DF and leakage current increased significantly.

[0154] Comparative Example 7

[0155] The manufacturing method of Comparative Example 7 is substantially the same as that of Example 1, except that the electrolytic paper is cotton pulp fiber.

[0156] The aluminum electrolytic capacitor prepared in Comparative Example 7 was subjected to a ripple life test of 2000 hours and a 105°C high temperature storage test of 1000 hours. The performance test after the test is shown in Table 13 below.

[0157]

[0158] It can be seen from Table 13 that the electrolytic paper is changed to cotton pulp fiber. Since the hydrogen bonding force between the fibers is relatively small, the high temperature can be tolerated for a short time. After the ripple life test, not only the capacity decreases significantly, but also the DF and ESR increase significantly, and the aluminum shell bulges; after the high temperature storage test, the DF and leakage current increase significantly.

[0159] Comparative Example 8

[0160] The manufacturing method of Comparative Example 8 is substantially the same as that of Example 1, except that the electrolytic paper is hemp fiber.

[0161] The aluminum electrolytic capacitor prepared in Comparative Example 8 was subjected to a ripple life test of 2000 hours and a 105°C high temperature storage test of 1000 hours. The performance test after the test is shown in Table 14 below.

[0162]

[0163] It can be seen from Table 14 that the electrolytic paper is changed to hemp fiber. Although it has low DF and ESR and good liquid absorption effect, its life is not long. After the ripple life test, not only the capacity decreases significantly, but the DF and ESR increase significantly, and the aluminum shell bulges; after the high temperature storage test, the DF and leakage current increase significantly.

[0164] The above-mentioned embodiments merely express the implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the patent scope of the present invention. Any technical solution obtained in the form of equivalent replacement or equivalent transformation shall fall within the protection scope of the present invention.

Claims

1. A method for manufacturing an aluminum electrolytic capacitor, characterized in that: It includes the following steps: Step S1, making a core package: inserting electrolytic paper between the anode foil and the cathode foil, and winding them into a core package; wherein the specific capacitance of the anode foil is 0.67-0.70 μF / cm 2 , thickness 110~125μm, specific volume discreteness ≤10%, tensile strength ≥16.7N / cm; Step S2, drying treatment: baking and drying the wound core package; Step S3, electrolyte impregnation: immerse the core package dried in step S2 into the electrolyte for impregnation treatment, wherein the electrolyte is composed of the following components by mass percentage: main solvent 45%-68%, auxiliary solvent 15%-25%, solute 8%-15%, additive 5%-12%, getter 0.8%-2%, repair agent 0.3%-1%; Step S4, heating and polymerization: heating and polymerization of the core package impregnated in step S3; Step S5, packaging step: wrapping the core polymerized in step S4 into a shell and sealing with a rubber plug; after sealing, the height between the top of the waist groove on the shell and the top of the curling edge is controlled to be 4.0±0.3mm, and the glue insertion depth of the curling edge is 40%-60% of the thickness of the rubber plug; Step S6, aging step; The main solvent is composed of the following components by mass percentage: ethylene glycol 45-67%, propylene glycol 22-35%, diethylene glycol 5-20%; The auxiliary solvent is composed of the following components by mass percentage: 50-62% ammonium dicarboxylate, 18-30% phosphotungstic acid, and 10-25% polyethylene glycol; The solute is composed of the following components by mass percentage: 35-55% ammonium adipate, 15-25% ammonium acetate, 10-22% citric acid, 5-14% 1.10-ammonium sebacate, and 3-10% 1.6-dodecanedioic acid; The additive is composed of the following ingredients by mass percentage: 30-45% nitrotrinitroborane, 18-32% 8-hydroxyquinoline, 12-25% nitrilotriacetic acid, and 5-15% tributyl phosphate; The repair agent is composed of the following components by mass percentage: 45-70% polyvinyl alcohol, 18-30% ammonium sebacate, 3-18% sodium hydroxide, and 1-8% sodium hypophosphite.

2. The method for manufacturing an aluminum electrolytic capacitor according to claim 1, wherein: The anode foil is an anode foil that has undergone six-stage chemical treatment.

3. The method for manufacturing an aluminum electrolytic capacitor according to claim 1, wherein: The rubber plug is prepared by mixing Teflon coated bakelite and EPDM rubber.

4. The method for manufacturing an aluminum electrolytic capacitor according to claim 1, wherein: The electrolytic paper is wood pulp fiber.

5. An aluminum electrolytic capacitor, characterized in that: The invention is prepared by the manufacturing method described in any one of claims 1 to 4.

Citation Information

Patent Citations

  • Method for preparing 1xxx-series cathode foil for aluminum electrolytic capacitors

    WO2020199610A1